Retraction: 7-nitroindazole, a selective neuronal nitric oxide synthase inhibitor in vivo prevents kainate-induced intrahippocampal neurotoxicity. Radenović L, Selaković V, Božić B. Arch Biol Sci. 2005;57(2)75-81. DOI: 10.2298/ABS0502075R - Editorial (Archives of Biological Sciences, 2016)
The article: 7-Nitroindazole, a selective neuronal nitric oxide synthase inhibitor in vivo prevents kainate-induced intrahippocampal neurotoxicity. Radenović L, Selaković V, Božić B. Arch Biol Sci. 2005;57(2)75-81, repeats data already published in: 7-Nitroindazole reduces nitrite concentration in rat brain after intrahippocampal kainate-induced seizure. Radenović L, Vasiljević I, Selaković V, Jovanović M. Comp Biochem Physiol Pt. C. 2003;135 443-50, without any referencing. Link to the retracted article 10.2298/ABS0502075R